(3GdHjGf aj cTa CSQGQ GdWH ddYjGfs - (3GdSeGf , eMeO Hf CMeO Hf eMeO GdMehj GdMSjfj GdMfajs ((3jMj Hf TeS GdOjf GdegOhi , Hf GdEeGe GdMSf ? s)
(3ChdgG (B:s
(3GdMeO ddg HdG HOGjI , hGdCNQ HdG fgGjI , Ndb GdNdb HbOQJg hHGSW GdQRb HQMeJg , GdeGf Ydi GdYHGO (B( (3HaVdI hQCaJg (B) s
(3BNQgG (B:s
(3hdjfg MJi jPgH GdeGA hjfbi GdOgf , hTQHJg Edi efbGdjf JeJ GdebGdI GdNGeSI hHJeGSgG Je GdcJGH s
(3YGT ai GdbQf GdSGHY GdgLQi CdaI dCHi GdaJM YeQ Hf CHj GdefUhQ jhSa Hf YeQ Hf Ydi Hf QShds
(3fGdJ edhc Hfi QShd ai Gdjef Sfg (B696 (3hbSeI Zdi NeS ebGdGJ eaUdI HaUhds
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B7s
Keywords: (3GdWHs